Is Occupational Mobility in Germany Hampered by the Dual Vocational System? The Results of a British-German Comparison - Rhein, Thomas [Verfasser]; Trübswetter, Parvati [Verfasser]; Nisic, Natascha [Verfasser] (My University, 2013)
"We compare occupational mobility in Germany and Britain and focus on the effects of the German dual vocational system. Based on a comparison of mobility rates for different occupations within each country and between the two countries, we find that mobility is particularly low in German apprenticeship occupations and conclude that the dual system impedes occupational changes. However, German mobility rates are also lower in non-apprenticeship occupations, and only a small part of the overall low mobility rate in Germany (almost three times lower than in Britain) can be attributed to the apprenticeship system. We conclude that institutions such as employment protection are more important for explaining cross-country differences in mobility. Moreover we find evidence for the claim that occupational mismatching at the beginning of working lives is more widespread in Britain." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.3.3 Mobilität; I 2.1 Deutschland; I 2.2.1 Westeuropa; Berufliche Mobilität; Einflussfaktor; Duales System; Internationaler Vergleich; Bundesrepublik Deutschland; Großbritannien